Loving the land that feeds you: an ethnographic investigation of volunteers in a community food garden - Madinga, Nolizwe (My University, 2018)
The city is thought by many people to be an opportunity to create a life of economic and social freedom. However, with South Africa being one of the most economically disparate countries in the world, this does not always materialise. Instead of being a place where people realise their potential and live their dreams as envisaged the city looms with poverty. The dire situation in the city forces people to find creative ways to survive. One such survival mechanism is urban agriculture. Urban agriculture allows city dwellers to plant their own produce or raise livestock and as a result not have to pay the rising cost of food. In a city that is ideal for agriculture, where there is plenty of vacant land, people can plant fruit and vegetables and also graze their livestock. However, the reality is that space is hugely contested in the city and this means that people who need to plant produce and graze livestock may not be able to do so, because they do not have the money to acquire land. Thus, urban agriculture done on a scale large enough to feed a substantial amount of people is often done by organisations on behalf of those people that are in need. The organisations train people and provide them with the skills that they need to produce food. Often times the workers are beneficiaries themselves. The workers get the produce as the fruit of their labour. That said, not all workers on urban agricultural projects work for food. The workers at Ministry of Helps work for monetary remuneration, albeit a little amount. They do not take the produce for themselves. This paper is an attempt to find out why the workers work on the project if they do not get the produce and they are not paid an amount of money that the workers perceive as enough. In this paper I seek to find out what the workers’ motivations are.
Submitted in partial fulfillment of the requirements for the degree Master of Arts by Coursework and Research Report Faculty of Humanities School of Social Sciences Department of Anthropology , March 2018
Keywords: Urban agriculture--South Africa; Food security--South Africa; Land use, Urban--South Africa; Sustainable development--South Africa